[LB.01.03] COMPARISON OF THE SPHYGMOCOR XCEL WITH APPLANATION TONOMETRY FOR CENTRAL PRESSURE ASSESSMENT IN CHILDREN AND ADOLESCENTS. (September 2017) - Stabouli, S.; Zervas, C.; Printza, N.; Dotis, J.; Chrysaidou, K.; Maliachova, O.; Antza, C.; Kotsis, V.; Papachristou, F.
Abstract : Objective: Over the last few years assessment of central systolic BP (cSP) has been increasing used in adults and seems to be superior to peripheral blood pressure (pBP) to predict cardiovascular events. The gold-standard technique is tonometry, but this technique can be challenging, especially when used on children. The purpose of this study was to validate cBP assessment with novel oscillometric SphygmoCor XCEL device for use in children and adolescents. Design and method: Children and adolescents aged 6–20 years were recruited subsequently and were equally distributed in two age groups (pre-adolescent children and adolescents). Central systolic BP (cSPton) was measured by applanation tonometry with the "convetional" Sphygmocor device and by SphygmoCor XCEL device (cSPosc). For each patient, the average of the three recordings taken with each device was calculated. Bland-Altman plots were generated for comparison of the tonometer- to oscillometric-based method. The ANSI/AAMI/ISO 2013 criteria were used to assess the accuracy of agreement between devices. Results: Five participants were excluded from the analysis due to low quality of recordings, four with tonometric technique and one with both devices. The remaining 67 participants had mean age 11.5 ± 3.7 years, were 31 (46.3%) male, and presented even distribution of sex in both age groups. cSPosc was strongly correlated with cSPton (R2 = 0.87, P < 0.001). Mean cSPton was 103.23 ± 9.43 mmHg and mean cSPosc 103.54 ± 8.87 mmHg. The mean cSP difference between the two devices was -0.30 ± 3.34 mmHg (P = NS), and fulfilled the AAMI criterion 1 (difference < 5.0 ± 8.0 mmHg). The estimated s.d. (inter-subject variability) was 2.17 mmHg. Bland-Altman analysis showed good agreement with LoA -6.24 to 6.84. No proportional bias was detected by linear regression analysis with dependent variable the mean differences between devices and independent variable mean cSP of the two devices (B = 0.06, P = NS). Conclusions: The new oscillometric SphygmoCor XCEL device provides equivalent results for cSP values to those obtained by tonometry in children and adolescents. Thus, the SphygmoCor XCEL device is appropriate for assessing cSP in the pediatric population.